Risk factors for severe dental anxiety among medical students - Janković, Slobodan; Aleksić, Dragana; Bahtijari, Zulfer; Jelić, Anica; Klačar, Jelena; Kovačević, Aleksandra; Mijailović, Nataša; Milovanović, Olivera; Petrović, Aleksandra; Radovanović, Ana; Sovrlić, Miroslav; Ružić Zečević, Dejana (Vojnosanitetski pregled, 2013)
Background/Aim. Severe dental anxiety (SDA) is the most severe form of dental anxiety, thus the aim of this study was to determine the factors associated with SDA in students of health-related disciplines. Methods. In this case-control study the cases were students with severe dental anxiety. The study was conducted at the Faculty of Medical Sciences, University of Kragujevac, Serbia. The participants were undergraduate students attending lectures during spring semester 2010/2011 (n = 1,812). A random sample of 800 students was assessed for the association between various risk factors and the severe dental anxiety. The main outcome measures were the data on demographics, dental anxiety, habits concerning oral hygiene, nutrition, general anxiety and (co)morbidity which were collected from the study participants by semi-structured questionnaire. Results. Less frequent visits to the dentist (OR adjusted = 7.02 [2.65; 18.60]) and visiting the dentist only when there is a dental problem (OR adjusted = 8.08 [1.28; 50.93]) were associated with severe dental anxiety. The same was true for improper oral hygiene (OR adjusted = 4.25 [1.16; 15.60]). Factors as changing toothbrush more frequently (OR adjusted = 0.33 [0.14; 0.76]) and having chronic disease (OR adjusted = 0.01 [0.00; 0.09]) were inversely associated with severe dental anxiety. The level of education of students was not associated with severe dental anxiety. Conclusion. Inappropriate oral hygiene, less frequent changes of a toothbrush and less frequent visits to the dentist are important risk factors for severe dental anxiety
Keywords: dental anxiety; students; medical; oral hygiene; dental care